1964
DOI: 10.1099/00221287-35-1-61
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of the Interactions between Flocculent Cells in the Flocculation of Saccharomyces cerevisiae

Abstract: SUMMARYThe flocculation of a strain of brewers' yeast was absolutely dependent upon the presence of calcium; a concentration of 200 mM-CaC1, was sufficient to ensure almost complete flocculation. No other metal could replace calcium ; several metals aggregated potentially flocculent cells but also aggregated non-flocculent cells. Sodium ions antagonized the action of the calcium. The effects of pH value and esterification suggested that carboxyl groups were involved. The flocs had a ' melting temperature ' of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
81
0
4

Year Published

1976
1976
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(94 citation statements)
references
References 7 publications
9
81
0
4
Order By: Relevance
“…Harris (I 959) postulated intercellular bonding in which bivalent cations link carboxyl groups in adjacent cells. Mill (1964b) largely agreed with Harris (1959) but suggested that the floc is stabilized by co-operative hydrogen bonding involving hydroxyl groups on the cell-surface polysaccharide. Recent work by Stewart, Russell & Garrison (1975) furnished additional evidence for the formation of carboxyl-Ca2+ complexes in yeast flocs, and they suggested that the carboxyl groups involved are in acidic wall proteins.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Harris (I 959) postulated intercellular bonding in which bivalent cations link carboxyl groups in adjacent cells. Mill (1964b) largely agreed with Harris (1959) but suggested that the floc is stabilized by co-operative hydrogen bonding involving hydroxyl groups on the cell-surface polysaccharide. Recent work by Stewart, Russell & Garrison (1975) furnished additional evidence for the formation of carboxyl-Ca2+ complexes in yeast flocs, and they suggested that the carboxyl groups involved are in acidic wall proteins.…”
Section: Introductionsupporting
confidence: 73%
“…Organisms which had been deflocculated by washing in deionized water or EDTA regained the ability to form flocs when CaCl, (0.1 yo, w/v) was included in the deionized water in which the rate was measured. Treating organisms with the esterifying agent 1,2-epoxypropane (Mill, 1964b ;Lyons & Hough, 1970 b) lowered the rate of floc sedimentation of all four strains after they had been treated with HF. This r,z-epoxypropane Table I +- The standard error of the means was less than 2 %.…”
Section: Eflect Of Hf On Wall Compositionmentioning
confidence: 99%
“…Para que a floculação se desenvolva é necessária a presença de íons cálcio [10] e também a movimentação entre as células, para que se acelere o processo de floculação, provavelmente devido ao aumento da coli-são entre as células, facilitando a adesão [8,19]. Os resíduos de aminoácidos da superfície de Lactobacillus fermentum e resíduos de carboidratos das leveduras são os responsáveis pelo desenvolvimento do fenôme-no da floculação [3,14].…”
Section: -Introduçãounclassified
“…To date, three mechanisms have been suggested to explain yeast flocculation: the colloidal 30 , Ca 2+ bridge 26 and zymolectin model theory 25,29 . Currently, the zymolectin model theory is widely accepted to explain yeast flocculation.…”
Section: Introductionmentioning
confidence: 99%